2021
DOI: 10.3390/ijms222111883
|View full text |Cite
|
Sign up to set email alerts
|

Differential Clearance of Aβ Species from the Brain by Brain Lymphatic Endothelial Cells in Zebrafish

Abstract: The failure of amyloid beta (Aβ) clearance is a major cause of Alzheimer’s disease, and the brain lymphatic systems play a crucial role in clearing toxic proteins. Recently, brain lymphatic endothelial cells (BLECs), a non-lumenized lymphatic cell in the vertebrate brain, was identified, but Aβ clearance via this novel cell is not fully understood. We established an in vivo zebrafish model using fluorescently labeled Aβ42 to investigate the role of BLECs in Aβ clearance. We discovered the efficient clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Real-time in vivo analysis in zebrafish allows the investigation of the clearance capacity of Amyloid-β isoform 42 (Aβ 1-42 ). Remarkably, Jeong et al (2021) demonstrated that the dynamic uptake of Aβ 42 depends on its aggregation status, where Aβ 1-42 monomers are selectively internalized and cleared by perivascular LECs but not Aβ 1-42 oligomers. The discovery of these isolated LECs in the surface of the brain involved in the homeostasis and uptake of Aβ peptides provides new therapeutic avenues in AD, where the enhancement of their function in combination with the reduction of Aβ aggregates might contribute to new approaches to prevent their accumulation.…”
Section: Non-lumenized Lecs In the Surface Of Zebrafish Brain And Mam...mentioning
confidence: 98%
“…Real-time in vivo analysis in zebrafish allows the investigation of the clearance capacity of Amyloid-β isoform 42 (Aβ 1-42 ). Remarkably, Jeong et al (2021) demonstrated that the dynamic uptake of Aβ 42 depends on its aggregation status, where Aβ 1-42 monomers are selectively internalized and cleared by perivascular LECs but not Aβ 1-42 oligomers. The discovery of these isolated LECs in the surface of the brain involved in the homeostasis and uptake of Aβ peptides provides new therapeutic avenues in AD, where the enhancement of their function in combination with the reduction of Aβ aggregates might contribute to new approaches to prevent their accumulation.…”
Section: Non-lumenized Lecs In the Surface Of Zebrafish Brain And Mam...mentioning
confidence: 98%
“…The ability to visualize these lymphatics in vivo may make this a useful model for studying their function. Brain lymphatic endothelial cells that do not form a lumen have been described and Jeong et al [ 82 ] found that those cells take up monomeric β-amyloid42 and were involved in clearing it from the zebrafish brain.…”
Section: Elements Of the Blood–brain Barrier Neurovascular Unit And B...mentioning
confidence: 99%
“…Baidya A TK et al [3] and Jeong YM et al [4] both investigated the activities of Aβ in physiology. In the first paper, the authors provide new insight into cholinergic dysfunction, which is known to be central to the pathology of Alzheimer's disease [5].…”
mentioning
confidence: 99%